Preservation with Different Smoking Techniques to Extend the Shelf Life of “Urutan” Chicken - AA Made Semariyani; Sudiarta, I Wayan; Singapurwa , Ni Made Ayu Suardani; Suariani, Luh (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
“Urutan” chicken is one of the processed meat products processed through the manufacture of meat dough, fat and complete Balinese spices (